Aplicación de contabilidad comercial en la distribuidora C y C en el cantón Yantzaza, período: mayo – junio/2016 - imenez Zhanay, Silvana Carolina J (2017)
The present research work was carried out as a prerequisite to obtaining the degree of Accounting and Auditing Engineer, Auditor Public Accountant according to the Regulations of the National University of Loja. It also contributed to its owner, in such a way that she was able to know what the real economic benefits were in the study period, which were determined through the execution of the accounting process. In compliancGe with the proposed objectives, the literature was prepared, which serves as support for the elaboration and support of the same, in practice the permanent account system was applied; starting from an Initial Inventory that was used to determine the stock of all the assets owned by the company, then a plan and manual of accounts that facilitated the identification and proper use of the accounts was developed, main and auxiliary records were applied to centralize and quantify the economic movement to finally present the Financial Statements that demonstrate in a clear and real way the economic results obtained in the period. Once the entire accounting process was completed, it was concluded that the Distributor obtained profit during the period under investigation; before which it is recommended that the owner implements the accounting process, which will be very useful so that at any time know their real balances and this way they will allow them to make sound decisions for their own benefit.